Anaerobic digestion of the microalga Spirulina at extreme alkaline conditions: biogas production, metagenome, and metatranscriptome - Nolla-Ardevol, Vimac; Strous, Marc; Tegetmeyer, Halina E. (Frontiers in Microbiology, 2015)
A haloalkaline anaerobic microbial community obtained from soda lake sediments was used to inoculate anaerobic reactors for the production of methane rich biogas. The microalga Spirulina was successfully digested by the haloalkaline microbial consortium at alkaline conditions (pH 10, 2.0 M Na+). Continuous biogas production was observed and the obtained biogas was rich in methane, up to 96 %. Alkaline medium acted as a CO2 scrubber which resulted in low amounts of CO2 and no traces of H2S in the produced biogas. A hydraulic retention time of 15 days and 0.25 g Spirulina L-1 day-1 organic loading rate were identified as the optimal operational parameters. Metagenomics and metatranscriptomics analysis showed that the hydrolysis of the supplied substrate was mainly carried out by Bacteroidetes of the “ML635J-40 aquatic group” while the hydrogenotrophic pathway was the main producer of methane in a methanogenic community dominated by Methanocalculus.